Diagnostic MALDI-TOF MS can differentiate between high and low toxic Staphylococcus aureus bacteraemia isolates as a predictor of patient outcome. Issue 8 (23rd August 2022) - Brignoli, Tarcisio; Recker, Mario; Lee, Winnie W. Y.; Dong, Tim; Bhamber, Ranjeet; Albur, Mahableshwar; Williams, Philip; Dowsey, Andrew W.; Massey, Ruth C.
Abstract : Staphylococcus aureus bacteraemia (SAB) is a major cause of blood-stream infection (BSI) in both healthcare and community settings. While the underlying comorbidities of a patient significantly contributes to their susceptibility to and outcome following SAB, recent studies show the importance of the level of cytolytic toxin production by the infecting bacterium. In this study we demonstrate that this cytotoxicity can be determined directly from the diagnostic MALDI-TOF mass spectrum generated in a routine diagnostic laboratory. With further development this information could be used to guide the management and improve the outcomes for SAB patients.